2017
DOI: 10.1002/2016jf004062
|View full text |Cite
|
Sign up to set email alerts
|

Bed load transport and boundary roughness changes as competing causes of hysteresis in the relationship between river discharge and seismic amplitude recorded near a steep mountain stream

Abstract: Hysteresis in the relationship between bed load transport and river stage is a well‐documented phenomenon with multiple known causes. Consequently, numerous studies have interpreted hysteresis in the relationship between seismic ground motion near rivers and some measure of flow strength (i.e., discharge or stage) as the signature of bed load transport. Here we test this hypothesis in the Erlenbach stream (Swiss Prealps) using a metric to quantitatively compare hysteresis in seismic data with hysteresis record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 84 publications
(172 reference statements)
3
44
0
Order By: Relevance
“…Therefore, seismic monitoring may be a tool to quantify macroturbulent eddies and associated flow resistance in complex natural channels. The results of this study are consistent with those of Roth et al (2017), who suggested changes in channel morphology as a source for water turbulence-associated hysteresis in natural channels. This study also implies that the Gimbert et al (2014) model will under-20 predict seismic energy released in rivers with complex channels and macroturbulent eddies.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, seismic monitoring may be a tool to quantify macroturbulent eddies and associated flow resistance in complex natural channels. The results of this study are consistent with those of Roth et al (2017), who suggested changes in channel morphology as a source for water turbulence-associated hysteresis in natural channels. This study also implies that the Gimbert et al (2014) model will under-20 predict seismic energy released in rivers with complex channels and macroturbulent eddies.…”
Section: Resultssupporting
confidence: 92%
“…The theoretical scaling relationship between water-generated vertical component power ( ) and discharge ( ) for water turbulence alone with a simple channel geometry is ∝ 1.25 (Gimbert et al, 2014;Gimbert et al, 2016). Roth et al 2017, found a ∝ rough channel geometry with variable width, the flow depth is a function of discharge, channel shape, and flow resistance (Leopold et al, 1960). Therefore, determining the causes of the scaling exponent change is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Roth et al. ), previous theory and its application at a natural scale suggest that the bedload and turbulent flow sources may be distinguished by analyzing ground motion at various frequencies and river‐to‐station distances (Gimbert et al. ; Cook et al.…”
Section: Introductionmentioning
confidence: 99%